Shotgun proteomic analysis of two Bartonella quintana strains. Issue 8 (15th March 2013) - Fabietti, Alessandra; Gaspari, Marco; Krishnan, Shibu; Quirino, Angela; Liberto, Maria Carla; Cuda, Giovanni; Focà, Alfredo; Figeys, Daniel
<x xml:space="preserve">Abstract</x> This study reports the first extensive shotgun analysis of the Bartonella quintana proteome. Proteins extracted from two B. quintana strains, Oklahoma and JK31, were analyzed in triplicate analyses by a bottom‐up approach consisting of tryptic digestion in SDS‐containing buffer, strong cation‐exchange StageTip fractionation, and nano‐LC‐MS/MS analysis. By setting spectral false discovery rate below 0.5%, 548 unique proteins were identified overall, of which 409 protein identifications were shared between the two strains. The data set, which achieves the highest proteome coverage for B. quintana to date, could be exploited for the quantitative analysis of a selected subset of target proteins.